Comparison of the colour and colourfastness of cotton fabric dyed with Archidendron Jiringga using the typical dyeing and mordanting methods / Zuraidah Hashim - Hashim, Zuraidah (2015)
The study investigated the effects of different methods of application of mordanting and dyeing of cotton fabric with dyes from the Archidendron Jiringga. The methods of application of mordants used includes pre mordanting, meta mordanting and post mordanting. The effects on cotton were analyzed based on the shade and the colourfastness to washing, light, perspiration and crocking. Aqueous extraction method was used to extract the dye. The study showed that for all the mordanting methods, the colour produced on the cotton fabric is uneven brown colour and meta mordanting method gave the best result in term of shade compared to the other methods. In term of the colourfastness, post mordanting gave the best result for wash fastness and pre mordanting gave the best result of crocking fastness. For perspiration colourfastness, pre mordanting and post mordanting gave the best colourfastness and for light fastness, post mordanting method gave the best colourfastness.